2014
DOI: 10.1016/j.jclepro.2014.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The role of collaboration in the UK green supply chains: an exploratory study of the perspectives of suppliers, logistics and retailers

Abstract: Role of collaboration in green supply chains in the UK: An exploratory study on suppliers, logistics and retailers perspectivesMany companies around the world have started to realise that working alone will not be sufficient in their move towards a greener supply chain (SC). More specifically, recent UK government regulations on implementing strict CO2 reduction encourage SC operators to work collaboratively, in production and logistics or other operations, to achieve their green objectives. In this research, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 28 publications
1
84
1
Order By: Relevance
“…The growing demand for improved service levels and rising costs for offering better quality products recognize collaboration in the supply chain as a key driver to increase business performance and sustainability [3,6,18,24].…”
Section: Collaboration For Sustainability In the Food Supply Chain (Fsc)mentioning
confidence: 99%
See 2 more Smart Citations
“…The growing demand for improved service levels and rising costs for offering better quality products recognize collaboration in the supply chain as a key driver to increase business performance and sustainability [3,6,18,24].…”
Section: Collaboration For Sustainability In the Food Supply Chain (Fsc)mentioning
confidence: 99%
“…Then, collaboration for supply chain sustainability is described. At the basic level, supply chain collaboration refers to companies and/or organizations working together to solve problems and/or achieving common goals [3,4,7]. However, supply chain collaboration is difficult to manage because of challenges regarding the decisions surrounding with whom and when to collaborate, for what reasons and how to implement collaboration [4].…”
Section: Collaboration For Sustainability In the Food Supply Chain (Fsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a growing research in the role of supply chain (SC) collaboration on sustainability (Vachon and Klassen, 2008;Ramanathan et al, 2014;Grekova et al, 2015;Gunasekaran et al, 2015). However, there have been limited studies on SCM practices of Small and Medium-Sized Enterprises (SMEs) (Quayle, 2003;Saad et al, 2006;Lenny Koh et al, 2007;Vaaland and Heide, 2007;Thakkar et al, 2009) and only a few studies on GSCM practices of SMEs (Aragon-Correa et al, 2008;Lee, 2008;Huang et al, 2012;Lee et al, 2012;Bourlakis et al, 2014;Huang et al, 2015), and no research has been found on UK food retail SMEs that has a particular focus on GSCM.…”
Section: Introductionmentioning
confidence: 99%
“…In the business models of many markets today the detrimental effects of immoral behavior are often manifested outside of the legal, geographical, and national boundaries of the company in which they are performed (e.g. Alkaya and Demirer, 2014;Ramanathan et al, 2014). The application is called moral decoupling (MDec) and provides a theoretical base to understand the dissonance discussed above from a supply chain perspective.…”
mentioning
confidence: 99%